2009
DOI: 10.1152/ajpgi.90599.2008
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and fate of ganglioside GD3 in human intestinal Caco-2 cells

Abstract: Ganglioside GD3 is a glycosphingolipid found in colostrum, developing tissues, and tumors and is known to regulate cell growth, differentiation, apoptosis, and inflammation. Feeding a GD3-enriched diet to rats increases GD3 in intestinal lipid rafts and blood. The mechanism, efficiency, and fate of ganglioside absorption by human enterocytes have not been investigated. A model to study GD3 uptake by human intestinal cells was developed to test the hypothesis that enterocyte GD3 uptake is time and concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…Uptake of ganglioside in vitro and in the intestine occurs by micelle absorption, monomer insertion, or receptor‐mediated uptake 49 . Metabolic kinetics of GD3 have been described in Caco‐2 cells 1 . Schnabl et al 1 have shown that GD3 is taken up by the intestinal brush‐border membrane and is mainly metabolized into new ganglioside species, with smaller portions being retained or transferred, whereas GD3 taken up by the basolateral membrane is not retained or transferred to any significant degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uptake of ganglioside in vitro and in the intestine occurs by micelle absorption, monomer insertion, or receptor‐mediated uptake 49 . Metabolic kinetics of GD3 have been described in Caco‐2 cells 1 . Schnabl et al 1 have shown that GD3 is taken up by the intestinal brush‐border membrane and is mainly metabolized into new ganglioside species, with smaller portions being retained or transferred, whereas GD3 taken up by the basolateral membrane is not retained or transferred to any significant degree.…”
Section: Discussionmentioning
confidence: 99%
“…Safety and bioavailability of ganglioside have been demonstrated in several experimental models 1 . ‐ 4 Uptake of ganglioside has been shown in Caco‐2 intestinal epithelial, 1 breast, 2 and prostate cancer cells 3 in vitro and in rat brain, plasma, and intestine 4 in vivo. Safety of ganglioside for human consumption is presumed as ganglioside is a component of foods such as human breast milk, meat, and dairy 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Several tissues have been shown to incorporate dietary gangliosides. Caco-2 cells incorporate GD3 [22] when provided with ganglioside in vitro [23]. Ganglioside uptake also occurs in several tissues in vivo .…”
Section: Ganglioside In Dietmentioning
confidence: 99%
“…Metabolic kinetics of GD3 has been described in depth in Caco-2 cells. GD3 taken up by the brush border membrane is mainly metabolized into new ganglioside species, with smaller portions being retained or transferred, whereas GD3 taken up by the basolateral membrane is not retained or transferred to any significant degree [22]. These observations suggest that each species of ganglioside localizes to particular regions of the enterocyte to carry out specific functions, which depend on site of uptake.…”
Section: Ganglioside In Dietmentioning
confidence: 99%
“…29,[31][32][33][34][35][36][37][38][39][40][41] To gain an understanding of ganglioside metabolism, studies have injected gangliosides into animals and monitored ganglioside fate. Before cell uptake, gangliosides occur in aqueous solutions in the form of micelles, monomers, and oligomers.…”
Section: Metabolism Of Gangliosidesmentioning
confidence: 99%